Contours of an Ethics of Environmental Transitions - Ferrari, Sylvie (International Transitions, 2024)
This article o¤ers a reflection on the ethical dimension of environmental transitions in the Anthropocene. Considering environmental transitions in relation to this new geological era, it analyzes the relationships between economic activities and nature on a biospheric scale. Environmental transitions are not independent of the transformations occurring within them and are part of societal development. In this context, preserving the habitability conditions of the biosphere is essential for any environmental transition and inseparable from how societies behave towards nature.